Investigation of Neuroprotective and Therapeutic Effects of Hesperidin in Experimental Spinal Cord Injury - Yurtal, Ziya; Altug, Muhammed Enes; Unsaldi, Emine; Secinti, Ilke Evrim; Kucukgul, Altug (Turkish Neurosurgical Soc, 2020)
AIM: To investigate the neuroprotective and therapeutic efficacy of hesperidin against secondary damage following traumatic spinal cord injury. MATERIAL and METHODS: A total of 32 male Wistar albino rats weighing 250-300 g were randomly divided into four groups (n=4): group I, control group; group II, sham group; group III, preconditioning group, and group IV, treatment group. A rat model of spinal cord injury was established by dropping a weight of 100 g/cm on the spinal cord exposed at T7-T10 with dorsal laminectomy. In neurological examination after the trial period, inclined planed test, modified Tarlov scale, and finger extension test were performed. Furthermore, the bioefficacy of hesperidin was investigated histopathologically, biochemically, and immunohistochemically using blood and tissue samples obtained from the experimental animals. RESULTS: Neurological examination following spinal cord injury revealed that hesperidin significantly contributed to improvement in the 24-hour period. Biochemical analyses revealed that hesperidin showed anti-inflammatory effects by decreasing IL-1 beta and TNF-alpha levels at the 24th hour as well as strong antioxidant activity by increasing TAS levels in groups III and IV. Histopathologically, hesperidin reduced hemorrhage, laceration, axonal and neuronal degeneration, necrosis, inflammatory reaction, and edema in groups III and IV. Immunohistochemically, hesperidin reduced the number of caspase 3-positive apoptotic cells in groups III and IV. CONCLUSION: Hesperidin showed antioxidant, anti-inflammatory, and anti-apoptotic effects during the acute period following spinal cord injury; thus, hesperidin shows neuroprotective and therapeutic efficacy in spinal cord injury.
1st International Veterinary Biochemistry and Clinical Biochemistry Congress -- APR 18, 2018 -- Hatay, TURKEY
Keywords: Spinal cord injury; Hesperidin; Oxidative stress; Apoptosis; Caspase-3; Rats